KOREAN COMMUNITY AS A CULTURAL DIPLOMACY OF THE REPUBLIC OF KOREA IN INDONESIA: A CASE STUDY ON KSCC COMMUNITY - Zahidi, M. Syaprin (IJRDO - Journal of Social Science and Humanities Research, 2017)
The expansion of the Republic of Korea culture usually called by Hallyu actually showed significant result in Indonesia. The significance of cultural expansion can be recognized by spread of Korean communities established in several cities of Indonesia, such as Running Man Lovers, Forever Dance Centre Jakarta (FDC Kpop dance cover), UI Hangugo Dongari, etc. The researcher observed that the Republic of Korea utilizing all sources to expand its culture in Indonesia through cultural exhibition shows by Korean Culture Center (KCC), Korean Drama broadcast by Television Stasions in Indonesia, etc. The researcher concluded that the success of cultural diplomacy of the Republic of Korea in Malang city can be identified through the establishment of Korean community, Korean Studies and Culture Center (KSCC).